Perilaku Kebersihan Diri (Personal Hygiene) Santri di Pondok Pesantren Wilayah Kabupaten Brebes akan Terwujud Jika Didukung dengan Ketersediaan Sarana Prasarana - Zakiudin, Ahmad; Shaluhiyah, Zahroh (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTThe Behavior Of Personal Hygiene Student at The Islamic Boarding School District in Brebes is Reached If The Availability of infrastructure and facilities of personal hygiene. To improve the health of students should be effort to improve personal hygiene behavior with the final result decrease morbidity rate of infectious disease. The aim of the studi is to analyze the factors that influence the personal hygiene students at the Islamic boarding school district Brebes. The study is quantitative and explanatory research with cross sectional approach. The population of the study is all of the junior and high school at the four Islamic boarding school as many as 3.350 students. Whereas samples were taken by Proportional cluster random sampling as many as 293 students. Data collection is taken by interviews and observations. The results of the univariate analysis describes that the behavior of personal hygiene students at the Islamic boarding school at Brebes District is good category (42,0%), less than the unfabvorable category is 58,0%. The results of bivariate analysis with Chi Square analysis showed that there are nine variables significantly associated. The variables are, gender, knowledge, availability of facilities and infrastructure of personal hygiene, availability regulations on personal hygiene, provision of information or dissemination, carer support boarding school, Support of friend, support health personel and support the ministry of religion. The most dominant factors that influence is the availability of facilities and infrastructure of personal hygiene (OR=10.335).Keyword : personal hygiene behavior, students, cottage